Implementasi Akhlak Profetik dalam Komunikasi Interpersonal Nabi Ibrahim AS - Taufik - Rahman (IAIN Padangsidimpuan, 2023)
AbstractProphetic communication and morals are often based on communication patterns and the values contained in them that were built by the Prophet Muhammad in his interactions in this life. Studying and drawing prophetic communication and morals long before the time of Prophet Muhammad SAW, namely during the time of Prophet Abraham AS, is certainly an interesting study. How the approach of prophetic morality was carried out by Prophet Ibrahim AS in his interpersonal interactions with Prophet Ismail AS depicted in the Koran is an important part of the implementation of prophetic morals which also needs to be emulated. The cultivation of noble prophetic moral values in communication as exemplified by Prophet Ibrahim AS through showing affection to the communicant in conveying messages, being open in hearing the opinions of other parties, not being hasty in executing ideas so as to make joint commitments and agreements that occur are the main points that can be exemplified from the prophetic morals shown from the communication of Prophet Ibrahim AS. AbstrakKomunikasi dan akhlak profetik sering disandarkan dengan pola komunikasi dan nilai yang terkandung di dalamnya yang dibangun oleh baginda Rasul SAW dalam interaksinya di kehidupan ini. Mengulik dan menarik komunikasi dan akhlak profetik jauh sebelum zaman Nabi Muhammad SAW yaitu pada zaman Nabi Ibrahim AS tentu menjadi kajian yang menarik. Bagaimana pendekatan akhlak profetik yang dilakukan Nabi Ibrahim AS dalam interaksinya secara interpersonal dengan Nabi Ismail AS yang terlukis di dalam Alquran adalah bagian penting dari implementasi akhlak profetik yang juga perlu diteladani. Penanaman nilai akhlak profetik yang luhur dalam komunikasi yang dicontohkan Nabi Ibrahim AS melalui penunjukan kasih sayang kepada komunikan dalam menyampaikan pesan, terbuka dalam mendengar pendapat pihak lain, tidak tergesa-gesa dalam mengeksekusi gagasan hingga melakukan komitmen bersama dan kesepakatan yang terjadi adalah poin utama yang bisa diteladani dari akhlak profetik yang ditampilkan dari komunikasi Nabi Ibrahim AS.